Evaluation of late adolescent pregnancies: Is late adolescence a risk factor for preterm labor? - DİZİ IŞIK, AYLİN; ANIK İLHAN, GÖKÇE; ÇELİK, İPEK; SOYSAL, SUAH (TAYLOR & FRANCIS LTD, 2019)
Study objective: We evaluated effect of late adolescence during pregnancy and its confounding factors on neonatal and maternal results. Objective: The aim of the present study is to evaluate the effect of late adolescence on maternal, perinatal outcomes and preterm labor. Methods: This retrospective study was carried out on 172 late adolescents and 160 adult women who delivered in a tertiary center. The demographic features, obstetrical and neonatal properties of the patients were analyzed. Results: Marital status, education levels, preeclampsia-eclampsia, gestational diabetes mellitus (GDM), urinary tract infections during pregnancy, intrauterine growth restriction, bleeding in last trimester, postpartum hemorrhage, perinatal mortality incidence, and mode of delivery for both groups were similar. Regular antenatal follow up and hemoglobin levels during admission to hospital were low in late adolescents. Anemia during pregnancy, preterm labor incidence was high for late adolescents compared with adults. When a logistic regression analysis was made for preterm labor, lack of antenatal follow up, urinary tract infection during pregnancy and history of still birth was risk factors for preterm labor rather than age. Conclusion: We assume that regular antenatal follow up can reduce preterm labor among late adolescents.
Keywords: Pregnancy complications; pregnancy in adolescence; preterm labor; TEENAGE PREGNANCIES; PERINATAL OUTCOMES; NEONATAL OUTCOMES; WOMEN